Visionary automation of sack handling and emptying. - Kavoussanos, M. (IEEE Robotics and automation magazine)
Describes an inexpensive yet ?intelligent? prototype system using vision-guided robotics for depalletizing and emptying polyethylene sacks. It uses structured light, and ultrasonics to obtain depth information. A structure is presented that is designed and built to minimize costs and increase reliability of the whole system, while at the same time fully automating the depalletizing and emptying of polyethelene sacks. The system is built around a conventional PC that carries out the tasks of control, vision, gripping, and fault monitoring. Simple PID loops are used for the control of all the robot axes, while an inexpensive vision system is used for the determination of the orientation of the pallets. A pneumatic gripper is used for the lifting of the sacks. The most probable faults are monitored for and appropriate actions are taken in the event of fault occurrence. In this way, a form of intelligence is built into the system